Door to door Selling Program Management on the Entrepreneurship Subject (A Site Study at SMK N 2 Purbalingga) - Handayani, Sri Pinuji (2011)
The objectives of this study are (1) to describe the characteristic of the teachers' activity in the door to door selling program on the entrepreneurship subject at SMK N 2 Purbalingga. (2) to describe the student' characteristic in the door selling program on the entrepreneurship subject at SMK N 2 Purbalingga. Type of this study is a qualitative study using ethnography design. This study was conducted at SMK N 2 Purbalingga. Data Collection method used in depth interview, participation obsevation, and documentation. Data analysis used a data analysis model arranged in a site to be described. Testing data validity used credibility, transferability, confirmability, and dependability. The results of this study are (1) Teachers of SMK N 2 Purbalingga are active in the door to door selling program on the entrepreneur subject. The teachers' activeness is seen from the preparation done, where teachers socialize and give the door to door selling theory in learning. Mental training is also provided by teachers through motivating and asking students to stimulate the door to door selling activity. Teachers conduct cooperation with the supplier or distributor such as PT Indomarco, PT Wingsfood, PT Ultra Prima Abadi (OT), PT Mayora Indah Tbk, and others. Teachers ask students to take the product from supplier when the teachers have completed an agreement with the supplier. To know whether the door to door selling activity run well or not, teachers control the students' activity through the students' weekly report and give solution to students who find some problems in performing the program. Teachers assess the implementation of the program by checking the product sold, income achieved, benefit got, and the accuracy of the payment to the supplier. (2) Students of SMK N 2 Purbalingga are active in the door to door selling program of the entrepreneur subject. Students follow the preparation activities including learning activity and briefing. Students take the product from the supplier and promote it directly to the customer the will. Students conduct direct promotion in front of the customer, if they find a difficult customer, they will look for another customer such as seller, retailer, even looking for customer who have a celebration. Students persuade and convince the customer to buy the product offered by allowing the customer to pay with a credit system. Students of SMK N 2 Purbalingga conduct the door to door selling program professionally. It is proved from the income they get. Students can exceed the specified target, they will get the more score from KKM and get bonus in form of money and voucher. Keywords: activity, door to door selling, teacher,